2008
DOI: 10.1539/joh.l8043
|View full text |Cite
|
Sign up to set email alerts
|

Effort‐Reward Imbalance and Depression in Japanese Medical Residents

Abstract: Effort-Reward Imbalance and Depression in Japanese Medical Residents: Yumi SAKATA, et al. Department of Occupational Mental Health, Graduate School of Medical Sciences, Kitasato University-The effort-reward imbalance is an important psychosocial factor which is related to poor health among employees. However, there are few studies that have evaluated effort-reward imbalance among medical residents. The present study was done to determine the association between psychosocial factors at work as defined by the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
6
25
1
8
Order By: Relevance
“…Mental stress is an important issue in contemporary occupational health and one that has been receiving increasing attention in Japan during recent years. Potentially high rates of psychosocial stresses suggested in the current study are supported by previous research which found that depressive symptoms affected around 28% of Japanese medical resi- dents 41) . Another study of medical residents also found that depressive symptoms were associated with NSI events 13) , while a Korean investigation revealed that HCW who had sustained an NSI experienced higher scores of depression and anxiety 42) .…”
Section: Discussionsupporting
confidence: 85%
“…Mental stress is an important issue in contemporary occupational health and one that has been receiving increasing attention in Japan during recent years. Potentially high rates of psychosocial stresses suggested in the current study are supported by previous research which found that depressive symptoms affected around 28% of Japanese medical resi- dents 41) . Another study of medical residents also found that depressive symptoms were associated with NSI events 13) , while a Korean investigation revealed that HCW who had sustained an NSI experienced higher scores of depression and anxiety 42) .…”
Section: Discussionsupporting
confidence: 85%
“…This is different from studies performed in other countries. For example, Sakata et al 3) reported that 12.2 and 44.4% of medical resi- dents in Japan experienced effort/reward imbalance and overcommitment, whereas Conway et al 8) reported that 16.1 and 26.3% of health-care workers in Italy experienced effort/reward imbalance and overcommitment. A survey of a group of nurses in the ORSOSA study in France identified effort/reward imbalance in 10.7% of the nurses and overcommitment in 40.8% of the nurses 19) .…”
Section: Discussionmentioning
confidence: 99%
“…(e.g., day shift switched to evening or night shift) (2) How many days off did you receive when you switched from the night shift to other shifts? (3) In the last 2 months, how many night shifts did you work? (4) In the last 2 months, how many times did you work 7 consecutive days per month?…”
Section: Shift Work Schedule Arrangement and Workloadmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its unique conditions, however, residency exemplifies the definition of effort-reward imbalance, i.e. high-cost/low-gain conditions, which have been associated with adverse health outcomes [15]. Further discussion of stress effects on attendings is beyond the scope of this article.…”
Section: The Importance Of Resident Well-beingmentioning
confidence: 99%